The Role of Islamic Education in the Development of Transformative Leadership and Human Resource Management in Madrasah. - Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2024)
This study explores the role of Islamic education in fostering transformative leadership and enhancing human resource management (HRM) within the context of madrasah. As educational institutions rooted in Islamic values, madrasahs face unique challenges and opportunities in cultivating leaders who are not only effective managers but also spiritual guides and agents of change. By integrating the principles of Islamic education—such as amanah (trust), ikhlas (sincerity), shura (consultation), and rahmah (compassion)—into leadership practices, madrasahs can build a culture of ethical governance and sustainable development. This paper highlights the importance of aligning HRM strategies with Islamic pedagogical values to nurture competent, committed, and visionary educators and administrators. The findings suggest that transformative leadership in madrasah is most effective when it is grounded in Islamic ethics, supports teacher development, encourages participatory decision-making, and fosters a holistic educational environment. The study contributes to the discourse on leadership in Islamic educational institutions and provides a framework for integrating faith-based values into contemporary HRM and leadership practices.